-9x+5x+12=-4x+3+8

Simple and best practice solution for -9x+5x+12=-4x+3+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+5x+12=-4x+3+8 equation:


Simplifying
-9x + 5x + 12 = -4x + 3 + 8

Reorder the terms:
12 + -9x + 5x = -4x + 3 + 8

Combine like terms: -9x + 5x = -4x
12 + -4x = -4x + 3 + 8

Reorder the terms:
12 + -4x = 3 + 8 + -4x

Combine like terms: 3 + 8 = 11
12 + -4x = 11 + -4x

Add '4x' to each side of the equation.
12 + -4x + 4x = 11 + -4x + 4x

Combine like terms: -4x + 4x = 0
12 + 0 = 11 + -4x + 4x
12 = 11 + -4x + 4x

Combine like terms: -4x + 4x = 0
12 = 11 + 0
12 = 11

Solving
12 = 11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4(x-5)=2(-2x+10) | | 11x+3=-15x+3 | | 2(x-1)=4x+9 | | 0,5x+4=-0,5x+3 | | 2x+10=-3x+10+5 | | 1/2x+4=-1/2x+3 | | kx^2+3x-5=0 | | 5(x-3)=6(x+12) | | X^3-5x=o | | 6(x-3)=3(2x-6) | | 4(x-5)=3x+15 | | 2ln(x+3)-3ln(x+2)+ln(x+1)=0 | | 11x+21=7x-31 | | (x+13)(x+13)=7 | | y=1400-50x | | 5x-9=5x+10 | | x^3+8x^2-7x=0 | | ax(1+x)-7x+9=0 | | 15j=450 | | -9x-4=3x+8 | | 10x-5x+6=22+3x-2x | | ax+ax^2=0 | | 6x-8=3x+19 | | 6x-3=17+x | | 2x+9=5x-4x+18 | | ax^2+(a-4)x+7=3x-2 | | 4-2y=36 | | 10x-3x+4=49+3x-x | | 2ax^3-7x=-9 | | -2(x+3)=7-(x+2) | | 25x^2-15x+3=0 | | 6m+10=28 |

Equations solver categories